Germline intergenic duplications at Xq26.1 underlie Bazex–Dupré–Christol basal cell carcinoma susceptibility syndrome. (12th September 2022) - Liu, Yanshan; Banka, Siddharth; Huang, Yingzhi; Hardman‐Smart, Jonathan; Pye, Derek; Torrelo, Antonio; Beaman, Glenda M.; Kazanietz, Marcelo G.; Baker, Martin J.; Ferrazzano, Carlo; Shi, Chenfu; Orozco, Gisela; et al.
Abstract: Background: Bazex–Dupré–Christol syndrome (BDCS; MIM301845) is a rare X‐linked dominant genodermatosis characterized by follicular atrophoderma, congenital hypotrichosis and multiple basal cell carcinomas (BCCs). Previous studies have linked BDCS to an 11·4‐Mb interval on chromosome Xq25‐q27.1. However, the genetic mechanism of BDCS remains an open question. Objectives: To investigate the genetic aetiology and molecular mechanisms underlying BDCS. Methods: We ascertained multiple individuals from eight unrelated families affected with BDCS (F1–F8). Whole‐exome (F1 and F2) and genome sequencing (F3) were performed to identify putative disease‐causing variants within the linkage region. Array comparative genomic hybridization and quantitative polymerase chain reaction (PCR) were used to explore copy number variations, followed by long‐range gap PCR and Sanger sequencing to amplify the duplication junctions and to define the head–tail junctions. Hi‐C was performed on dermal fibroblasts from two affected individuals with BDCS and one control. Public datasets and tools were used to identify regulatory elements and transcription factor binding sites within the minimal duplicated region. Immunofluorescence was performed in hair follicles, BCCs and trichoepitheliomas from patients with BDCS and sporadic BCCs. The ACTRT1 variant c.547dup (p.Met183Asnfs*17), previously proposed to cause BDCS, was evaluated with t allele frequency calculator. Results: In eight families with BDCS, we identified overlapping 18–135‐kb duplications (six inherited and two de novo ) at Xq26.1, flanked by ARHGAP36 and IGSF1 . Hi‐C showed that the duplications did not affect the topologically associated domain, but may alter the interactions between flanking genes and putative enhancers located in the minimal duplicated region. We detected ARHGAP36 expression near the control hair follicular stem cell compartment, and found increased ARHGAP36 levels in hair follicles in telogen, in BCCs and in trichoepitheliomas from patients with BDCS. ARHGAP36 was also detected in sporadic BCCs from individuals without BDCS. Our modelling showed the predicted maximum tolerated minor allele frequency of ACTRT1 variants in control populations to be orders of magnitude higher than expected for a high‐penetrant ultra‐rare disorder, suggesting loss of function of ACTRT1 variants to be an unlikely cause for BDCS. Conclusions: Noncoding Xq26.1 duplications cause BDCS. The BDCS duplications most likely lead to dysregulation of ARHGAP36. ARHGAP36 is a potential therapeutic target for both inherited and sporadic BCCs. What is already known about this topic? Bazex–Dupré–Christol syndrome (BDCS) is a rare X‐linked basal cell carcinoma susceptibility syndrome linked to an 11·4‐Mb interval on chromosome Xq25‐q27.1. Loss‐of‐function variants in ACTRT1 and its regulatory elements were suggested to cause BDCS. What does this study add? BDCS is caused by small tandem noncoding intergenic duplications at chromosome Xq26.1. The Xq26.1 BDCS duplications likely dysregulate ARHGAP36, the flanking centromeric gene. ACTRT1 loss‐of‐function variants are unlikely to cause BDCS. What is the translational message? This study provides the basis for accurate genetic testing for BDCS, which will aid precise diagnosis and appropriate surveillance and clinical management. ARHGAP36 may be a novel therapeutic target for all forms of sporadic basal cell carcinomas. Abstract : In this paper we show that Bazex‐Dupré‐Christol syndrome (BDCS), an X‐linked disorder of susceptibility to basal cell carcinomas, is caused by non‐coding Xq26.1 duplications that likely result in dysregulation of ARHGAP36, encoded by a flanking gene. Plain language summary available online